Extended treatment with interferon and ribavirin in a hemodialysis patient with chronic hepatitis C - Vigani,Aline Gonzalez (2010)
Hemodialysis patient with chronic HCV infection,who was started on monotherapy with interferon.Qualitative HCV RNA remained positive at 12 weeks of treatment; ribavirin was associated. HCV RNA was negative at week 24 and treatment was extended to 72 weeks. HCV RNA negative six months after treatment.